2017
DOI: 10.21873/anticanres.11933
|View full text |Cite
|
Sign up to set email alerts
|

Flattening Filter Free vs. Flattened Beams for Lung Stereotactic Body Radiation Therapy

Abstract: We report a low toxicity rate and a shortened beam on time in patients treated with 3D FFF SBRT for lung neoplastic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…FFF technique permits a considerable increase in the dose rate delivery and reduce treatment time by more than 50% compared to flattening filter (FF) technique without compromising the plan’s quality ( 23 , 25 , 26 ). Our study reported median beam-on-time of less than 2 minutes which was in line with previous VMAT-FFF studies conducted in patients with lung tumors ( 12 , 13 ). Decreased treatment time can improve treatment efficacy for SBRT because it reduces the likelihood of intrafraction motion and reduces the likelihood of undesirable patient motion during treatment.…”
Section: Discussionsupporting
confidence: 92%
“…FFF technique permits a considerable increase in the dose rate delivery and reduce treatment time by more than 50% compared to flattening filter (FF) technique without compromising the plan’s quality ( 23 , 25 , 26 ). Our study reported median beam-on-time of less than 2 minutes which was in line with previous VMAT-FFF studies conducted in patients with lung tumors ( 12 , 13 ). Decreased treatment time can improve treatment efficacy for SBRT because it reduces the likelihood of intrafraction motion and reduces the likelihood of undesirable patient motion during treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Intra-fraction imaging is recommended as best practice per ESTRO ACROP guidelines[29]. Because a faster treatment delivery time is likely associated with less patient movement and therefore more accurate treatment delivery, the use of a flattening-filter free setting can help to optimize treatment delivery as well[30-32]. The use of heterogeneity corrections has also been shown in RTOG 0236 to have a significant effect on prescription dose and tumor coverage, and should be considered standard in SBRT treatments[33].…”
Section: Discussionmentioning
confidence: 99%